Ações educativas e oralidade de matrizes africanas: saberes e fazeres - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The research through a Case Study, investigated the approach of Educational Actions and Orality of African Matrices with a view to cultural recognition for the construction of a reflection that transcends the simple concept of ethnic-racial relations linked to the Transculturality of marginalized peoples in our country. society, which include a large number of black, indigenous and other mixed-race people in the educational context. Specific projects are implemented to enhance the identity construction of mixed-race people, rescuing the African culture that greatly influences our society. Culturally, these educational actions are somewhat little applied within the training of individuals in schools. This study meets the cultural needs of rescuing Afro-Brazilian civilizational values within these orality in the educational context of teachers and high school students, in an Afro-Indigenous Library environment at the Santa Maria Educational Center, Administrative Region of Federal District - RA XIII, satellite city of the Federal District, develops the 365 Days of Black Consciousness Project. The General Objective of this work demonstrates that the Library promotes the African formative matrix in Brazilian Culture through the Teaching of Afro-Brazilian History and Culture. In this context, we list the following specific objectives: to locate historical and artistic information/knowledge regarding African Oral Tradition; verify its impact on the students involved; the Oral Tradition present in a Brazilian African-based religious community highlighting the educational and social possibilities present there; characterize the transfer of Afro knowledge and practices; highlight, in works and in the legal framework, the marks of African Oral Tradition and; reflect on how African Oral Tradition is present in the school environment. Problem: Has oral tradition been an indivisible part of the formative matrix of Brazilian culture for the teaching of history and Afro-Brazilian history? In relation to methodological procedures, it is a qualitative approach relying on field, bibliographic and documentary research. The purpose of exploratory qualitative research was to reveal and provide results that allow us to formulate a hypothesis. This method of investigation also enables a more comprehensive definition of the research problem. The choice of the sample will be intentional, due to its history of applicability to the issue of African Oral Tradition. The historical and referential data of Africanism (Altuna, 2014), its influence on the construction of Brazilian Culture and how this Culture fits into the transfer of oral knowledge within the school environment (Hernandez, 2015) was analyzed. The proposed methodological route of the research was the case study (Severino, 2007), with high school students and teachers being the object of study through interviews, surveys and historical analysis. The research traced a historical path of Brazilian African Orality, its Religiosity and its Educational scope (Lopes, 2008) The research concluded that the Library promotes anti-racist education and the mitigation of structural racism. The library enriches the school curriculum by integrating Afro-centered knowledge and deconstructing stereotypes. This interdisciplinary approach is important for the formation of critical citizens who are engaged in the fight against all forms of discrimination.
Educational actions and orality from african matrixes: knowing and doing
Keywords: Negro africano; Oralidade; Tradição oral; Saberes e fazeres; Black African; Orality; Oral tradition; Knowing and doing; CIENCIAS HUMANAS::EDUCACAO; FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO; FUNDAMENTOS DA EDUCACAO::ANTROPOLOGIA EDUCACIONAL; FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO; LINGUISTICA::LINGUISTICA HISTORICA